Two Row Wampum, Human Rights, and the Elimination of Tuberculosis from High-Incidence Indigenous Communities - Richard Long; Courtney Heffernan; Melissa Cardinal-Grant; Amber Lynn; Lori Sparling; Dorilda Piche; Mara Nokohoo; Diane Janvier (Harvard FXB Center for Health and Human Rights, 2019)
The Two Row Wampum belt is a symbolic record of the first agreement between Europeans and American Indians on Turtle Island (North America). The agreement outlined a commitment to friendship and peace between people living perpetually in parallel, with each party recognizing the other as an equal partner. Subsequent treaty relationships between the Indigenous peoples of the Canadian prairies and settler society, along with the colonially imposed structures they spawned, are widely regarded as having broken the Covenant Chain, the foundation of which is Two Row Wampum. For example, the universal right to health, especially public health, as protected by provincial and territorial legislation in Canada, is under threat in Indigenous communities with a high incidence of tuberculosis. The rights of Indigenous peoples have been asserted, and reasserted, in the United Nations Declaration on the Rights of Indigenous Peoples, the Truth and Reconciliation Commission of Canada, the International Patients' Charter for Tuberculosis Care, and Jordan's Principle. Herein we describe the implementation of a strategic plan that reinforces human rights and dignity in the spirit of Two Row Wampum in contemporary tuberculosis elimination efforts.